Sobrevivencia de “tectona grandis” (teca), durante el primer año de ejecución del programa de incentivos para la reforestación, en dos Provincias Del Ecuador. Año 2014 - Gavilánez Muñoz, Carlos Alberto (2016)
The research project survival "Tectona grandis" (teak), in different climatic conditions, was evaluated during the first year of implementation of the incentive program for reforestation, in the provinces of Los Rios and Guayas, established as sampling units (UM) throughout the study area. The survival of teak in the first year and behavior in climatic conditions, mainly based on gathering information from audits survivals program of forest incentives, use it as a tool for research and get the best benefits produce positive results of the proposed incentives for reforestation in our country. The analysis of T-student for survival in two locations, Guayas and Los Rios, which correspond to treatment, the test shows that there is no statistical difference between the two locations. In the province of Guayas with climatic conditions of average temperature of 25 ° C, and with an average rainfall of 1700 mm exposed values higher survival in most cantons as it is in El Empalme with 99% survival being the locality better behaved, followed by Bucay with 97% survival, but the win was the town with 75% survival on record the lowest percentage. In the province of Los Rios average temperature of 25 ° C, and an average rainfall of 1963 mm exhibits high values of survival in most cantons as it is in Quimsaloma with 99.21% survival followed by Buena Fe with 98.6% survival, however Quevedo, was the city with 82.91% survival.